New insights on partial trisomy 3q syndrome: de novo 3q27.1-q29 duplication in a newborn with pre and postnatal overgrowth and assisted reproductive conception - Gregorio Serra; Vincenzo Antona; Marcello Cimador; Giorgia Collodoro; Marco Guida; Ettore Piro; Ingrid Anne Mandy Schierz; Vincenzo Verde; Mario Giuffrè; Giovanni Corsello (BMC, 2023)
Abstract Background Duplications of the long arm of chromosome 3 are rare, and associated to a well-defined contiguous gene syndrome known as partial trisomy 3q syndrome. It has been first described in 1966 by Falek et al., and since then around 100 patients have been reported. Clinical manifestations include characteristic facial dysmorphic features, microcephaly, hirsutism, congenital heart disease, genitourinary anomalies, hand and feet abnormalities, growth disturbances and intellectual disability. Most of cases are due to unbalanced translocations, inherited from a parent carrying a balanced aberration (reciprocal translocation or inversion), and rarely the genomic anomaly arises de novo. Very few studies report on the prenatal identification of such rearrangements. Case presentation Hereby, we report on a newborn with a rare pure duplication of the long arm of chromosome 3. Noninvasive prenatal test (cell free fetal DNA analysis on maternal blood), performed for advanced parental age and use of assisted reproductive technique, evidenced a partial 3q trisomy. Then, invasive cytogenetic (standard and molecular) investigations, carried out through amniocentesis, confirmed and defined a 3q27.1-q29 duplication spanning 10.9 Mb, and including about 80 genes. Our patient showed clinical findings (typical facial dysmorphic features, esotropia, short neck, atrial septal defect, hepatomegaly, mild motor delay) compatible with partial trisomy 3q syndrome diagnosis, in addition to pre- and postnatal overgrowth. Conclusions Advanced parental age increases the probability of chromosomal and/or genomic anomalies, while ART that of epigenomic defects. Both conditions, thus, deserve more careful prenatal monitoring and screening/diagnostic investigations. Among the latter, cell free fetal DNA testing can detect large segmental aneuploidies, along with chromosomal abnormalities. It identified in our patient a wide 3q rearrangement, then confirmed and defined through invasive molecular cytogenetic analysis. Neonatologists and pediatricians must be aware of the potential risks associated to duplication syndromes. Therefore, they should offer to affected subjects an adequate management and early and careful follow-up. These may be able to guarantee to patients satisfactory growth and development profiles, prevent and/or limit neurodevelopmental disorders, and timely recognition of complications.